2022
DOI: 10.1007/s43069-022-00135-x
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Leadership, Supply Chain Innovation, and Adaptability: A Cross-national Investigation

Abstract: This study investigates the effects of entrepreneurial leadership on supply chain innovation and supply chain adaptability. Based on theoretical foundations of the upper echelon theory and the dynamic capability theory, it also assesses the mediating role played by supply chain innovation in the relationship between entrepreneurial leadership and supply chain adaptability. Partial least squares structural equation modeling (PLS-SEM) was performed on survey data collected from 139 firms in Sudan, Japan, and Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…They continuously focus on improving the existing processes and also try to find new ones (Latif et al, 2020). Abdalla and Nakagawa (2022) considered EL as a dynamic capability that helps in proactively recognizing the opportunities and exploiting the resources throughout the supply chain resulting in increasing adaptability and innovation of the supply chain, resulting in enhanced performances. Witschel et al (2022) suggested that EL is motivated and promotes risk-taking and experimentation to discover and learn the new opportunities available in the changing environment.…”
Section: Literature Review 21 Supply Chain Resiliencementioning
confidence: 99%
See 3 more Smart Citations
“…They continuously focus on improving the existing processes and also try to find new ones (Latif et al, 2020). Abdalla and Nakagawa (2022) considered EL as a dynamic capability that helps in proactively recognizing the opportunities and exploiting the resources throughout the supply chain resulting in increasing adaptability and innovation of the supply chain, resulting in enhanced performances. Witschel et al (2022) suggested that EL is motivated and promotes risk-taking and experimentation to discover and learn the new opportunities available in the changing environment.…”
Section: Literature Review 21 Supply Chain Resiliencementioning
confidence: 99%
“…Abdalla and Nakagawa (2022) considered EL as a dynamic capability that helps in proactively recognizing the opportunities and exploiting the resources throughout the supply chain resulting in increasing adaptability and innovation of the supply chain, resulting in enhanced performances. Witschel et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the greatest overall societal, economic and political challenge of recent times has not yet been named: The climate change. Logistics has a crucial function in meeting this challenge by planning and operating sustainable value chains [6].…”
Section: Introductionmentioning
confidence: 99%